Dynamic self-assembly of detonation nanodiamond in water. Issue 9 (26th February 2020) - Chang, Shery L. Y.; Reineck, Philipp; Williams, Dewight; Bryant, Gary; Opletal, George; El-Demrdash, Samir A.; Chiu, Po-Lin; Ōsawa, Eiji; Barnard, Amanda S.; Dwyer, Christian
Abstract : We use direct imaging and dynamic light scattering to reveal the previously unknown dynamic self-assembly of detonation nanodiamond dispersions in water which have been purified without additional surface modification. Abstract : Nanodiamonds are increasingly used in many areas of science and technology, yet, their colloidal properties remain poorly understood. Here we use direct imaging as well as light and X-ray scattering reveal that purified detonation nanodiamond (DND) particles in an aqueous environment exhibit a self-assembled lace-like network, even without additional surface modification. Such behaviour is previously unknown and contradicts the current consensus that DND exists as mono-dispersed single particles. With the aid of mesoscale simulations, we show that the lace network is likely the result of competition between a short-ranged electrostatic attraction between faceted particles and a longer-ranged repulsion arising from the interaction between the surface functional groups and the surrounding water molecules which prevents complete flocculation. Our findings have significant implications for applications of DND where control of the aggregation behaviour is critical to performance.